A NOVEL TREATMENT OF DYE WASTEWATER OF BATIK INDUSTRY BY A COMBINATION OF ALUMINIUM SULFATE AND NATURAL IRON COATED-SAND - Izarul Machdar (Purifikasi, 2011)
This paper presents the results of dye wastewater treatment of a batik industry in a batch experiment. The experiment was carried out by adding a mixture of aluminium sulfate as coagulant and natural iron oxide-coated sand (NICS) into the wastewater. Sedimentation rate of the formed flock was enhanced by a magnet. Initial COD concentration of the dye wastewater of 1060 mg/L was used in the experiment. Results of this research showed that the efficiency of the dye removal and settling time were affected by iron sand entrapped in the formed flocks. The highest efficiency of COD removal was 95%, or similar to the final COD concentration of 45 mg/L at settling time of 10 minutes. It could be concluded that the combination of aluminium sulfate and NICS could effectively be used in the treatment of the dye wastewater from batik industry.